1987
DOI: 10.4319/lo.1987.32.1.0143
|View full text |Cite
|
Sign up to set email alerts
|

Resource depletion by active suspension feeders on tidal fiats: Influence of local density and tidal elevation1

Abstract: Sampling at two elevations from a tidal flat on the Shark Bay (Western Australia) shoreline at Monkey Mia revealed abundant suspension-feeding bivalves of numerous (> 17) species. Their total density increased by 3 x up the tidal elevation gradient from the subtidal margin of the flat to intertidal sites -97 cm higher. Factorial field experiments were used to test the effect of site (tidal elevation), local bivalve density, and their interaction on growth and survivorship of three species of suspension-feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
120
1
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(128 citation statements)
references
References 16 publications
4
120
1
3
Order By: Relevance
“…Structural complexity, however, has also been shown to facilitate predation (Micheli 1997). Their biological activities also have the potential to influence the structure of macrofaunal assemblages; suspensionfeeding can deplete the water column of food and larvae (Woodin 1976, Peterson & Black 1987, Petersen & Riisgard 1992, Andre et al 1993, and the deposition of faecal material may change the biogeochemical composition of their surrounding sediments (Klerks et al 1996, Peterson & Heck 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Structural complexity, however, has also been shown to facilitate predation (Micheli 1997). Their biological activities also have the potential to influence the structure of macrofaunal assemblages; suspensionfeeding can deplete the water column of food and larvae (Woodin 1976, Peterson & Black 1987, Petersen & Riisgard 1992, Andre et al 1993, and the deposition of faecal material may change the biogeochemical composition of their surrounding sediments (Klerks et al 1996, Peterson & Heck 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Growth, condition, reproduction, and metabolic rates of a population are integrated responses of adaptation to the environment, and several factors influence mussels' growth and survival in marginal environments. Supply of food is essential and depends on the horizontal advection, the concentration and vertical mixing of food particles, which are influenced by water velocity and the bottom roughness (Fr~chette et al, 1989), but also of importance are the duration of exposure to air (Seed, 1969;Peterson & Black, 1987), tolerance of desiccation during emersion (Kennedy, 1976) and stress caused by wave action (Harger, 1970). Further, the growth rate and the maximum size of M. edulis living in low saline areas (7 %0) are much lower than in high saline areas (28 %0), indicating that mussels in low saline areas suffer from a less favourable energy balance (Tedengren & Kautsky, 1986;Kautsky et aI., 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments as in Fig. 2 (1986) found that Macoma balthica was also unaffected by increased density, but other studies have demonstrated density-dependent growth for various bivalves (Broom 1982, Peterson 1982, Peterson & Black 1987, Peterson & Beal 1989, including P. fumatus, although this result was obtained at the artificially high densities used in aquaculture operations (Heasman et al 1998). The greater importance of inter-versus intraspecific effects on the growth of juvenile Pecten fumatus contrasts with the results of Peterson (1982), who found that interspecific effects were usually non-significant and consistently far smaller than intraspecific effects.…”
Section: Discussionmentioning
confidence: 53%
“…Food (or 'seston') limitation is thought to be responsible for density-dependent effects in other bivalves (Broom 1982, Peterson 1982, Peterson & Black 1987, Peterson & Beal 1989, and there is some quantitative evidence of seston depletion by intertidal bivalves (e.g. Fréchette & Bourget 1985, Peterson & Black 1991.…”
Section: Discussionmentioning
confidence: 99%